2012
DOI: 10.1111/j.1365-2966.2012.21322.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and nitrogen abundances of H iiregions in six spiral galaxies

Abstract: Spectroscopic observations of 63 H ii regions in six spiral galaxies (NGC 628, NGC 783, NGC 2336, NGC 6217, NGC 7331 and NGC 7678) were carried out with the 6‐m telescope (BTA) of Russian Special Astrophysical Observatory with the Spectral Camera attached to the focal reducer SCORPIO in multislit mode with a dispersion of 2.1 Å pixel−1 and a spectral resolution of 10 Å. These observations were used to estimate the oxygen and nitrogen abundances and the electron temperatures in H ii regions through the recent v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 62 publications
(117 reference statements)
0
34
1
Order By: Relevance
“…This equation fitted to the above data, including the central metallicity which we measure as 12 + log 10 (O/H) = 9.31 ± 0.18 using an SDSS spectrum taken at the center of the galaxy, gives 12 + log 10 (O/H) = 9.25 − 1.28 (r G /r 25 ) dex. This is a steeper gradient than the average for spirals (e.g., Pilyugin et al 2004;Gusev et al 2012). However, we note that in the above fit we are using the central oxygen abundance, without accounting for the possibility of AGN activity at the center of the galaxy.…”
Section: Metallicity Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…This equation fitted to the above data, including the central metallicity which we measure as 12 + log 10 (O/H) = 9.31 ± 0.18 using an SDSS spectrum taken at the center of the galaxy, gives 12 + log 10 (O/H) = 9.25 − 1.28 (r G /r 25 ) dex. This is a steeper gradient than the average for spirals (e.g., Pilyugin et al 2004;Gusev et al 2012). However, we note that in the above fit we are using the central oxygen abundance, without accounting for the possibility of AGN activity at the center of the galaxy.…”
Section: Metallicity Estimatesmentioning
confidence: 99%
“…13 Proposal ID 48-408, PI C. Fremling, conducted in service mode. Gusev et al (2012). The dashed blue line shows a firstorder polynomial fit which includes the central oxygen metallicity measured for NGC 5806 using an SDSS spectrum, and the dashed red line shows the same fit with the metallicity datapoint at the center of the galaxy excluded.…”
Section: Metallicity Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectroscopy data (line intensities and EW (Hβ)) for IC 2574 are taken from Croxall et al (2009), data for NGC 628 are partly from Gusev et al (2012) and partly from van Zee et al (1998), data for NGC 6946 are taken from Gusev, Sakhibov & Dodonov (2013), and NGC 925 and NGC 3184 data are taken from van Zee et al (1998). Finally, NGC 3621 data are from Ryder (1995).…”
Section: Spectroscopic Datamentioning
confidence: 99%
“…Ivanov et al (1992) observed and compiled a catalogue of positions, angular sizes, integral magnitudes and H II identification of 147 OB associations and aggregates in NGC 628. Numerous star formation regions have been studied earlier based on photometric, spectroscopic and spectrophotometric observations (McCall, Rybski & Shields 1985;Belley & Roy 1992;Ferguson, Gallagher & Wyse 1998;Bresolin, Kennicutt & Garnett 1999;Larsen 1999Larsen , 2004Bruevich et al 2007;RosalesOrtega et al 2011;Gusev et al 2012;Berg et al 2013).…”
Section: Ngc 628 Previous Studiesmentioning
confidence: 99%